分解因式: (1)-4a2+4a-1 (2)-4x2y+12xy2-9y3 (3)9(x-y)2-6(y-x)+1 (4)3-6x+3x2 (5)-a+2a2-a3 (6)(x2+y2)2-4x2y2 (7)a4-2a2b2+b4 (8)(
分解因式:
(1)-4a
2+4a-1
(2)-4x
2y+12xy
2-9y
3 (3)9(x-y)
2-6(y-x)+1
(4)3-6x+3x
2 (5)-a+2a
2-a
3 (6)(x
2+y
2)
2-4x
2y
2 (7)a
4-2a
2b
2+b
4 (8)(x
2+9)
2-36x
2 (9)
++n4 (10)-2ax
n-1-18ax
n+1+12ax
n.
優(yōu)質(zhì)解答
(1)原式=-(4a
2-4a+1)=-(2a-1)
2;
(2)原式=-y(4x
2-12xy+9y
2 )=-y(2x-3y)
2;
(3)原式=(3x-3y+1)
2;
(4)原式=3(1-2x+x
2)=3(1-x)
2;
(5)原式=-a(1-a)
2;
(6)原式=(x+y)
2(x-y)
2;
(7)原式=(a
2-2ab+b
2)(a
2+2ab+b
2)=(a+b)
2(a-b)
2;
(8)原式=(x
2+9-6x)(x
2+9+6x)=(x+3)
2(x-3)
2;
(9)原式=
n2(+n)2;
(10)原式=-2ax
n-1(1-6x+9x
2)=-2ax
n-1(1-3x)
2.
我來回答
類似推薦